LAND AND USE COVER CHANGE ASSESSMENT OF AN AGRICULTURAL AREA IN ROMANIA USING REMOTE SENSING AND CONSIDERING ENVIRONMENT CHANGE (PANGEEA, 2025)
ABSTRACT: The paper presents major aspects of the land use change. Changes in land coverage such as deforestation, agricultural expansion and urbanization have been identified to be not only a consequence of environmental change but also a significant cause driving further changes globally in response to the altering of biogeochemical cycles. Economic performance of Agriculture is therefore directly impacted by climatic conditions which invariably alter energy flows and consequently the performance, health and persistence of both crops and other land cover. This study intends to assess and compare the recent the land cover/land use within the small region of Crăciunelul de Jos, Romania using RS and GIS processing to provide localized insight regarding the environmental shifts and expansion of this region
Keywords: Land use; agriculture; GIS; Remote sensing